Analytické hodnotenie látky BL 443 pivalátu - Bezáková, Z; Stankovicová, M; Csöllei, J (Ceska a Slovenska farmacie, 2001)
The paper presents the results of an analytical evaluation and a study of some physicochemical properties of a new potential drug of the prodrug type--the substance BL 443 pivalate with an assumed antidysrhythmic effect. The structure of the substance has been confirmed by elemental analysis, IR and UV spectroscopy. The following parameters were determined: melting point, solubility, dissociation constant, experimental partition coefficient in four different systems, and surface activity. The chromatographic behaviour of the drug on a thin layer (adsorption and partition chromatography) was also investigated. Acidimetric titration in non-aqueous medium and spectrophotometry in the ultraviolet region of the spectrum at the wavelength of the second absorption maximum of the drug was employed to determine the content of the drug in pure substance.
Keywords: prekurzory léčiv; fyzikální chemie; valeráty; Anti-Arrhythmia Agents; Prodrugs; chemické jevy; Chemical Phenomena; antiarytmika; Valerates; Chemistry, Physical